IgLON5 deficiency produces behavioral alterations in a knockout mouse model - Landa, Jon; Serafim, Ana Beatriz; Alba, Mercedes; Maudes, Estibaliz; Molina-Porcel, Laura; Garcia-Serra, Anna; Mannara, Francesco; Dalmau, Josep; Graus, Francesc; Sabater, Lidia (Frontiers in Immunology, 2024)
Background Anti-IgLON5 disease is a neurological disorder characterized by autoantibodies against IgLON5 and pathological evidence of neurodegeneration. IgLON5 is a cell adhesion molecule of unknown function that is highly expressed in the brain. Our aim was to investigate the impact of IgLON5 loss-of-function in evaluating brain morphology, social behavior, and the development of symptoms observed in an IgLON5 knockout (IgLON5-KO) mouse model. Methods The IgLON5-KO mice were generated using CRISPR-Cas9 technology. Immunohistochemistry on fixed sagittal brain sections and Western blotting brain lysates were used to confirm IgLON5 silencing and to evaluate the presence of other cell surface proteins. Two- month-old IgLON5-KO and wild-type (WT) mice underwent a comprehensive battery of behavioral tests to assess 1) locomotion, 2) memory, 3) anxiety, 4) social interaction, and 5) depressive-like behavior. Brain sections were examined for the presence of anatomical abnormalities and deposits of hyperphosphorylated tau in young adult (2-month-old) and aged (22-month-old) mice. Results Mice did not develop neurological symptoms reminiscent of those seen in patients with anti-IgLON5 disease. Behavioral testing revealed that 2-month-old IgLON5-KO mice showed subtle alterations in motor coordination and balance. IgLON5-KO females exhibited hyperactivity during night and day. Males were observed to have depressive-like behavior and excessive nest-building behavior. Neuropathological studies did not reveal brain morphological alterations or hyperphosphorylated tau deposits. Conclusion IgLON5-KO mice showed subtle alterations in behavior and deficits in fine motor coordination but did not develop the clinical phenotype of anti-IgLON5 disease.